Synthesis, Spectroscopic Analysis and Antidiabetic Properties of Copper (II) Complex of Mangifera indica Leaf Crude Extract - Mary Adelaide Oladipo; Folasade Omobolanle Ajao; Adewusi John Adepoju; Kayode Taiwo Ishola; Olalekan Jamiu Ajeigbe (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Many applied conventional drugs in treating diabetes have been reported to possess some drawbacks which necessitate a search for alternative therapies. In order to search for a more active antidiabetic agent, this study synthesized and evaluated antidiabetic properties of Mangifera indica crude extract and its Cu (II) complex in alloxan-induced diabetic albino rats. The leaf crude extract and its metal complex were characterized using percentage metal analysis and IR spectroscopic data. Experimental animals were induced by a single intraperitoneal injection of Alloxan monohydrate at a single dose of 140 mg/kg body weight and animals with fasting blood glucose level (BGL) > 200 mg/dL were considered diabetic. Metformin was used as a standard drug. Fasting blood glucose level and body weight were used to assess the antidiabetic activity. One-way ANOVA was used to determine the level of statistically significant at p< 0.05. The crude extract was found to coordinate with the metal ion through O donor atom of C=O and O-H of phenol and ketone respectively. The Cu (II) complex of the crude extracts at tested dose of 600mg/kg demonstrated more antidiabetic activity without weight gain than the standard drug. It is concluded that the Cu (II) complex could be a potential material in the development of more active and negative-side-effect-free antidiabetic drug.